The Hanoverian succession dynastic politics and monarchical culture - Gestrich, Andreas 1952-; Schaich, Michael; Großbritannien, Hannover und Nordwestdeutschland im Zeitalter der Personalunion 1714-1837 (Ashgate, 2015)
Introduction / Michael SchaichPart I. Dynastic legacies -- The Hanoverian monarchy and the legacy of late Stuart kingship / Ronald G. Asch -- The House of Brunswick-Lüneburg and the Holy Roman Empire: the making of a patriotic dynasty, 1648-1714 / Martin Wrede -- Part II. Representing protestantism -- George I, the Hanoverian succession, and religious dissent / David Wykes -- Hanover-Britain and the Protestant cause, 1714-1760 / Andrew C. Thompson -- The Hanoverians and the colonial churches / Jeremy Gregory -- Part III. Image policies -- The Hanoverian monarchy and the culture of representation / Tim Blanning -- "Every inch not a king": the bodies of the (first two) Hanoverians / Robert Bucholz -- Monarchy, affection and empire: the Hanoverian dynasty in eighteenth-century America / Brendan McConville -- Visions of kingship in Britain under George III and George IV / G.M. Ditchfield -- Part IV. Contested loyalties -- The Hanoverian succession and the politicisation of the British army / Hannah Smith -- Jacobitism and the Hanoverian monarchy / Gabriel Glickman -- The alternative to the House of Hanover: the Stuarts in exile, 1714-45 / Edward Corp -- Radical popular attitudes to the monarchy in Britain during the French Revolution / Amanda Goodrich..